Review on Biodiesel Wastewater Treatment Using Membrane Bioreactor (MBR) Technology - Satbhai, Siddharth M.; Topare, Niraj S.; Bhutada, Dinesh S.; Bokil, Shantini A.; Wadgaonkar, Vinayak S.; Gunnasegaran, Prem (International Journal of Membrane Science and Technology, 2023)
Reclaiming and reusing water are both economically and environmentally significant concerns for enterprises to consider. The creation of biodiesel fuel is one of the outcomes of the development of technology that provide alternatives to fuel derived from petroleum. Most of the research done on biodiesel thus far has concentrated on its creation and fuel qualities, while environmental control has received very little attention. This review paper discusses biodiesel fuel production from edible oil, non-edible oil, animal fats, and other sources, as well as the transesterification process and the main source of biodiesel wastewater. With a growing population, depleting natural resources, and a plethora of environmental challenges, it is crucial that we find ways to reuse, recycle, and reproduce. This paper provides a summary of research done on the topic of recycling biodiesel wastewater. The pretreatment of wastewater from biodiesel production leads to an improvement in the efficiency of biological processes. By combining the biological process with membrane filtration, MBR technology is developed, which has many advantages over traditional approaches. This review has also examined the relevance, potential, and feasibility of using MBR Technology to treat biodiesel wastewater released from a biodiesel production process. Reusing wastewater after it has been treated with MBR Technology is a further feasible option.